First Fatal Oseltamivir-Resistant 2009 Pandemic Influenza A (H1N1) Case in an Adult in Korea - Hong, Seung-Dok (Chonnam National University Medical School, 2011)
It has been suggested that oseltamivir-resistant influenza viruses harboring the H274/275Y mutation are less virulent than are those that are oseltamivir-sensitive, and fatality attributed to infection with an oseltamivir-resistant virus is very rare. Here we report the first fatal adult case of oseltamivir-resistant 2009 pandemic influenza A (H1N1) in Korea. A 60-year-old Korean male who had hypertension, diabetes mellitus, chronic kidney disease, and dilated cardiomyopathy visited Chonnam National University Hospital because of a 7-day history of chest pain and dyspnea. The patient was at another clinic and had been medicated with oseltamivir (75 mg twice daily) beginning 7 days before admission. Empirical antibiotics were started on the first day of hospitalization. Reverse-transcriptase polymerase chain reaction for 2009 pandemic influenza A (H1N1) was reported to be positive, and a double dose of oseltamivir (150 mg twice per day) was started on day four of hospitalization. However, the pneumonia worsened and the patient died, despite 3 days of high-dose antiviral therapy and 6 days of antibacterial therapy. An H275Y mutation was detected in the neuraminidase gene sequence. This case shows that oseltamivir resistance after short-term drug exposure is possible and can be fatal, emphasizing that early use of zanamivir should be considered in suspicious cases.